2004
DOI: 10.1097/01.inf.0000142465.25992.c3
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic and Clinical Characteristics of Rotavirus Disease During Five Years of Surveillance in Venezuela

Abstract: This study confirms the significant impact of rotavirus disease in Venezuela. Rotavirus vaccines currently in development could diminish the morbidity associated with this common cause of childhood diarrheal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
41
3
9

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 26 publications
6
41
3
9
Order By: Relevance
“…The most vulnerable of all the age groups were the children who are below the age of five years and it has been observed that the children [5 years of age have considerably increased RV infection rate in comparison with the adults (P \ 0.0001). Studies have reported that the most RV infections in children occurs before the age of 2 years [1,10,32,36] and in this study also the children \2 years of age demonstrated highest rate (50 %) of RV infections among all the patients belonging to different stages of life. EV infection was evenly distributed between the children (\5 years old) and adult ([5 years old) patient groups.…”
Section: Discussionmentioning
confidence: 53%
“…The most vulnerable of all the age groups were the children who are below the age of five years and it has been observed that the children [5 years of age have considerably increased RV infection rate in comparison with the adults (P \ 0.0001). Studies have reported that the most RV infections in children occurs before the age of 2 years [1,10,32,36] and in this study also the children \2 years of age demonstrated highest rate (50 %) of RV infections among all the patients belonging to different stages of life. EV infection was evenly distributed between the children (\5 years old) and adult ([5 years old) patient groups.…”
Section: Discussionmentioning
confidence: 53%
“…In addition, G2 rotavirus infections at CHOP occurred twice as frequently in children <6 months of age than in children 6-12 months of age. To further complicate direct comparisons of our results with prior studies indicating that infection with rotavirus in young infants requiring a healthcare intervention is not uncommon (4,37,38), some publications do not clearly distinguish nosocomial from community-acquired acquisition. The methodological limitations of our analysis should be acknowledged.…”
Section: Discussioncontrasting
confidence: 41%
“…A clinical definition of watery diarrhea suggestive of rotavirus infection was developed based on the literature, and defined as a diarrhea episode with a maximum of four or more bowel movements per 24 hour period, with the presence of vomiting or fever (or both), and without any blood in the stool. [20][21][22][23][24][25] An episode was considered to be new if the participant experienced at least 3 days without an episode before the onset of a new episode. In addition to diarrhea episodes, breastfeeding status, and rotavirus vaccine status were also updated at each household visit.…”
Section: Methodsmentioning
confidence: 99%